In our time: Memoir of a revolution - Brownmiller, Susan (Dial Press, 1999)
There once was a time when the concept of equal pay for equal work did not exist, when women of all ages were "girls," when abortion was a back-alley procedure, when there was no such thing as a rape crisis center or a shelter for battered women, when "sexual harassment" had not yet been named and defined. "If conditions are right," Susan Brownmiller says in this stunning memoir, "if the anger of enough people has reached the boiling point, the exploding passion can ignite a societal transformation." In Our Time tells the story of that transformation, as only Brownmiller can. A leading feminist activist and the author of Against Our Will, the book that changed the nation's perception of rape, she now brings the Women's Liberation movement and its passionate history vividly to life. Here is the colorful cast of characters on whose shoulders we stand--the feminist icons Betty Friedan, Kate Millett, Germaine Greer, and Gloria Steinem, and the lesser known women whose contributions to change were equally profound. And here are the landmark events of the era: the consciousness-raising groups that sprung up in people's living rooms, the mimeographed position papers that first articulated the new thinking, the abortion and rape speak-outs, the daring sit-ins, the underground newspaper collectives, and the inventive lawsuits that all played a role in the most wide-reaching revolution of the twentieth century. Here as well are Brownmiller's reflections on the feminist utopian vision, and her dramatic accounts, rendered with honesty and humor, of the movement's painful internal schisms as it struggled to give voice to the aspirarations of all women. Finally, Brownmiller addresses that most relevant question: What is the legacy of feminism today?
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; droits des femmes*; fem1000; féminisme matérialiste; féminisme radical; histoire; mouvements féministes; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; témoignage; états-unis

Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge research in gender and history, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; cours; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Femmes du siècle - Institut de recherches et d'études féministes (FéminÉtudes, 1999)
Cette publication de 1999 porte sur l’histoire des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; discipline; féminétudes; histoire; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; thématiques

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; cours; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; sofia; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales